1992
DOI: 10.3177/jnsv.38.329
|View full text |Cite
|
Sign up to set email alerts
|

Metabolism of Arachidonic, Eicosapentaenoic, and Docosahexaenoic Acids in HepG2 Cells and Rat Hepatocytes.

Abstract: SummaryThe metabolism of arachidonic acid (AA), eicosapenta enoic acid (EPA), and docosahexaenoic acid (DHA) was examined in HepG2 cells, a human hepatoma cell line, and rat hepatocytes. The AA level in HepG2 cells was lower than in rat hepatocytes and incorporation of AA into HepG2 was also smaller than into rat hepatocytes. Both cells could not increase the level of cellular DHA by the addition of exogenous 22:5 (n-3); whereas, rat hepatocytes, but not HepG2 cells, increased the levels of AA from 20:3 (n-6) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
8
0

Year Published

1995
1995
2006
2006

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 11 publications
2
8
0
Order By: Relevance
“…In fact, retroconversion of DHA, which requires saturation of the 4 double bond by 2,4-enoyl-CoA reductase and peroxisomal chain shortening via limited ␤-oxidation, appears to be inhibited by DHA deficiency (Tocher and Dick, 2001). Retroconversion of DHA to 22:5n − 3 and EPA has been observed previously in various animal tissues (Schacky and Weber, 1985;Brossard et al, 1996) and different types of cultured cells (Rosenthal et al, 1991;Fujiyama-Fujiwara et al, 1992;Brown and Subbaiah, 1994). Further metabolic experimental studies using labelled fatty acids will be necessary to confirm this hypothesis.…”
Section: Discussionsupporting
confidence: 51%
“…In fact, retroconversion of DHA, which requires saturation of the 4 double bond by 2,4-enoyl-CoA reductase and peroxisomal chain shortening via limited ␤-oxidation, appears to be inhibited by DHA deficiency (Tocher and Dick, 2001). Retroconversion of DHA to 22:5n − 3 and EPA has been observed previously in various animal tissues (Schacky and Weber, 1985;Brossard et al, 1996) and different types of cultured cells (Rosenthal et al, 1991;Fujiyama-Fujiwara et al, 1992;Brown and Subbaiah, 1994). Further metabolic experimental studies using labelled fatty acids will be necessary to confirm this hypothesis.…”
Section: Discussionsupporting
confidence: 51%
“…The preservation of the desaturation potential is a major property of Y79 cells, unlike a number of other cancer cell lines. Many studies have shown that the polyunsaturated fatty acid synthesis may be partly or entirely inhibited following cell tumorization, notably through the loss of ⌬6and/or ⌬5-desaturation activity (Mathers and Bailey, 1975;Spector et al, 1979;Fujiyama-Fujiwara et al, 1992;Naval et al, 1993;Grammatikos et al, 1994Grammatikos et al, , 1995Bardon et al, 1996). In normal retina, it has been demonstrated in rodent and bovine that all enzymes for elongation and desaturation of 18:3n-3 to 22:6n-3 are present, although the final conversion of 22:5n-3 to 22:6n-3 is rate-limiting (Wetzel et al, 1991;Rotstein et al, 1996).…”
Section: Table V Fatty Acid Composition In Cell Phosphatidylethanolamentioning
confidence: 99%
“…Retroconversion of DHA to 22:5n-3 and EPA has been observed previously in various animal tissues [30][31][32] and retroconversion of DHA to 22:5n-3 and EPA, and 22:5n-3 to EPA has been reported in various cells in culture. 22,[33][34][35] In contrast, in rat U III (uterine stromal) cells, which show higher levels of DHA production from 18:3n-3 than most other cell lines, there was no significant retroconversion of DHA, added at 5 µM. 36 To our knowledge the effects of EFA deficiency on retroconversion processes in cell cultures has not been reported previously, but retroconversion of DHA to EPA and 22:5n-3 was reported to be increased in hepatocytes prepared from salmon fed an EFA deficient diet in comparison with hepatocytes from salmon fed an n-3PUFA supplemented diet.…”
mentioning
confidence: 99%